2008
DOI: 10.1089/aid.2007.0134
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Spread and Genetic Diversification of HIV Type 1 Subtype C in a Rural Area of Southern Mozambique

Abstract: In this study, we analyzed the human immunodeficiency type 1 (HIV-1) viruses circulating between 1999 and 2004 in antiretroviral-naive women from a rural area of southern Mozambique. Nucleotide sequencing of the HIV-1 long terminal repeat (LTR) U3, envelope (env) C2V3C3, and protease (pr) genomic regions was performed from women sera samples collected in 1999 and 2004. Phylogenetic analysis revealed that all amplified sequences belonged to subtype C. Although env sequences were predominantly CCR5-tropic (R5), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Maputo is the capital city of Mozambique and has the third highest HIV-1 prevalence rates in the country (23%, 18%-29%). 3 Unlike other studies investigating transmitted HIV drug resistance in Mozambique [27][28][29] and elsewhere in Africa, [21][22][23][24][25] the patients enrolled in our study could afford to pay for CD4 cell counts, for plasma viral load, and, eventually, for antiretroviral drugs. Moreover, they were, in general, severely immune compromised.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Maputo is the capital city of Mozambique and has the third highest HIV-1 prevalence rates in the country (23%, 18%-29%). 3 Unlike other studies investigating transmitted HIV drug resistance in Mozambique [27][28][29] and elsewhere in Africa, [21][22][23][24][25] the patients enrolled in our study could afford to pay for CD4 cell counts, for plasma viral load, and, eventually, for antiretroviral drugs. Moreover, they were, in general, severely immune compromised.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Phylogenetic analysis revealed that the C viruses circulating in Maputo are highly divergent and probably have been introduced into this city from diverse geographic regions. These results are consistent with previous findings demonstrating the existence of many subtype C sublineages in southern Africa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subtype C is the overwhelming prevailing strain in Southern Africa (Bartolo et al, 2009b;Gonzalez et al, 2010;Lahuerta et al, 2008;Papathanasopoulos et al, 2010), in India and neighbor countries (Neogi et al, 2009a;Neogi et al, 2009b) and in the southern region of Brazil (Monteiro-Cunha et al, 2011). Subtype D strains are found mainly in East Africa, and to a lesser extent in West Africa (Conroy et al, 2010;Harris et al, 2002;Laukkanen et al, 2000;Songok et al, 2004).…”
mentioning
confidence: 99%